A Conversation between Jacques Bouveresse and Hilary Putnam. (15th September 2020) - Bouveresse, Jacques; Putnam, Hilary
Abstract: The following interview took place between Jacques Bouveresse and Hilary Putnam on May 11, 2001 in Paris at the Collège de France. Sandra Laugier was present, preserved the transcription, and proposed that we publish the text here. It was translated into English by Marie Kerguelen Feldblyum LeBlevennec and lightly edited by Jacques Bouveresse, Juliet Floyd, and Sandra Laugier. Themes covered in the interview include the question of Wittgenstein's importance in contemporary philosophy, Putnam's development with respect to realism, especially in philosophy of mathematics, and the differences and motivations for realism in mathematics, physics, and ethics. The editors thank Marie Kerguelen Feldblyum LeBlevennec for her translation, and Jacques Bouveresse, Mario De Caro, and Sandra Laugier for permission to publish this transcription.